Distance‐ and near‐visual impairment in rural Chinese adults in Kailu, Inner Mongolia. (20th August 2015) - Cheng, Fang; Shan, Li; Song, Wulian; Fan, Pan; Yuan, Huiping
Abstract: Purpose: To investigate the prevalence and causes of distance‐visual impairment and near‐vision impairment in a rural Chinese population in Inner Mongolia. Methods: A population‐based, cross‐sectional study design was used to identify visual impairment in the Chinese aged 40 years and older living in Kailu County, Inner Mongolia. Low vision, blindness and near‐visual impairment (NVI) were defined according to World Health Organization (WHO) criteria. Results: The overall prevalence of blindness and visual impairment based on the presenting visual acuity (VA) was 2.2% (95% CI: 1.8–2.6) and 9.8% (95% CI: 8.9–10.6), respectively, and was adjusted to 0.9% (95% CI: 0.6–1.2) and 4.7% (95% CI: 4.1–5.3) using best‐corrected visual acuity (BCVA), respectively. Taking the presenting VA into consideration, the leading cause of visual impairment and blindness was cataract (40.3%, 40.9%), followed by uncorrected refractive error (26.6%, 28.2%). According to the BCVA, the main cause of visual impairment and blindness was cataract (48.3%, 41.3%) followed by glaucoma (19.0%, 23.9%). Among the examined subjects, 80.3% had NVI, and 51.7% had presbyopia. Major barriers reported by NVI persons without near correction were lack of money to purchase prescription glasses and poor quality of the available ones (43.2%). Conclusion: Visual impairment is a serious public health problem, and the main causes leading to visual impairment are treatable and preventable in the rural Chinese population in Inner Mongolia. Presbyopia, together with the low rate of spectacles and lack of appropriate refractive and presbyopia spectacles, is highly prevalent in rural China.